Understanding Society and Natural Resources Forging New Strands of Integration Across the Social Sciences - Manfredo, Michael J.; Vaske, Jerry J.; Rechkemmer, Andreas; Duke, Esther A. (Springer Netherlands : Imprint: Springer, 2014)
In this edited open access book leading scholars from different disciplinary backgrounds wrestle with social science integration opportunities and challenges. This book explores the growing concern of how best to achieve effective integration of the social science disciplines as a means for furthering natural resource social science and environmental problem solving. The chapters provide an overview of the history, vision, advances, examples, and methods that could lead to integration. The quest for integration among the social sciences is not new. Some argue that the social sciences have lagged in their advancements and contributions to society due to their inability to address integration related issues. Integration merits debate for a number of reasons. First, natural resource issues are complex and are affected by multiple proximate driving social factors. Single disciplinary studies focused at one level are unlikely to provide explanations that represent this complexity and are limited in their ability to inform policy recommendations. Complex problems are best explored across disciplines that examine social-ecological phenomenon from different scales. Second, multi-disciplinary initiatives such as those with physical and biological scientists are necessary to understand the scope of the social sciences. Too frequently there is a belief that one social scientist on a multi-disciplinary team provides adequate social science representation. Third, more complete models of human behavior will be achieved through a synthesis of diverse social science perspectives.